Amalan Maṭla’ al Hilal Menurut Pandangan Ahli Falak dalam Penentuan Kalendar Hijri: The Practice of Maṭla’ al-Hilal According to Astronomical Scholars in Determining the Hijri Calendar - Hashim, Muhammad Ridzuan; Mohd Nawawi, Mohd Saiful Anwar; Man, Sa’adan (Al-Basirah Journal, 2024)
Visibility of the young crescent moon in a single area of maṭla’ for determining the date of the Hijri Calendar is one of the processes that influence the Hijri Calendar. This process directly influences the Hijri Calendar practices and the timing of significant events such as Ramadan and Syawal celebrations. Determining the maṭla’ involves the precise observation of the young crescent moon, conducted by experts skilled in lunar cycles and equipped with established visibility criteria accordingly MABIMS criteria. This study explores the perspectives of Islamic astronomy scholars from Malaysia, Indonesia, and Brunei Darussalam on integrating traditional fiqh principles with contemporary astronomical tools in moon-sighting practices. A study was conducted to obtain the true meaning of maṭla’ that can be used by countries in the Southeast Asian region. The respondents were interviewed, and the study suggests that maṭla’ MABIMS can be used as a coordination instrument in the field.